3, 4‐Dinitrofurazan: Structural Nonequivalence of ortho‐Nitro Groups as a Key Feature of the Crystal Structure and Density. Issue 46 (8th December 2020) - Suponitsky, Kyrill Y.; Smol'yakov, Alexander F.; Ananyev, Ivan V.; Khakhalev, Artem V.; Gidaspov, Alexander A.; Sheremetev, Aleksei B.
Abstract: Being a liquid at room temperature, the crystalline form of 3, 4‐dinitrofurazan (DNF) has long been the subject of theoretical predictions. Its detonation performance in the solid state was calculated based on very high crystal density (1.89–2.02 g/cm 3 ) predicted by different theoretical schemes. Using zone melting technique, we were able to grow a DNF single crystal of suitable quality for X‐ray diffraction study. The experimental density was found to be 1.917 g/cm 3 at 100 K, which corresponds to 1.85 g/cm 3 at room temperature, that is lower than erlier predictions. We found that the ortho ‐nitro groups of DNF are not equivalent and behave differently upon the crystal structure formation, which was not taken into account in the theoretical estimates carried out earlier. It has now been shown that using the ΔOED ‐based densification approach, this "ortho ‐effect" can be clarified and quantified. The observed effect is probably characteristic of all polynitro compounds, where nitro groups are brought together, and should be kept in mind when constructing high density materials. Abstract : Crystal structure of dinitrofurazan (which melts at −15 °C) was determined. Experimental density appeared to be lower than earlier predictions by different molecule‐based approaches. Crystal packing analysis has revealed that two nitro groups (in ortho ‐position) densify differently upon crystal formation due to intramolecular steric repulsion. Such ortho ‐effect can be quantified and seems to be a characteristic feature of all polynitrocompounds.